2015
DOI: 10.1136/jclinpath-2015-203275
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA chromogenic in situ hybridisation signal pattern correlation with breast tumour pathology

Abstract: These data corroborate the involvement of three lncRNAs (HOTAIR, H19 and KCNQ1OT1) in breast tumourigenesis and support lncRNA CISH as a potential clinical assay. Importantly, CISH allows identification of the tissue compartment expressing lncRNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 18 publications
2
63
0
Order By: Relevance
“…MALAT1, a well-known lncRNA and possible oncogene (16), is upregulated in malignancies of multiple organs (10). RNA ISH enables direct visualization of lncRNAs, and strong MALAT1 hybridization signals were previous reported in breast malignancies (17). In this study, we examined the expression level of MALAT1 in normal thyroid tissue as well as benign and malignant neoplasms using ISH and real-time PCR validation.…”
Section: Discussionmentioning
confidence: 64%
“…MALAT1, a well-known lncRNA and possible oncogene (16), is upregulated in malignancies of multiple organs (10). RNA ISH enables direct visualization of lncRNAs, and strong MALAT1 hybridization signals were previous reported in breast malignancies (17). In this study, we examined the expression level of MALAT1 in normal thyroid tissue as well as benign and malignant neoplasms using ISH and real-time PCR validation.…”
Section: Discussionmentioning
confidence: 64%
“…ZFAS1 was originally identified a regulator of alveolar development and epithelial cell differentiation in the mammary gland [16], subsequently studies showed ZFAS1 was aberrantly down-regulated in breast cancer tissues and cells [16, 18, 19]. Recent studies have demonstrated that ZFAS1 was overexpressed in various cancer tissues and cell lines, and promoted the cancer progression through affecting the phenotypes of cancer cells and molecular pathways.…”
Section: Discovery Of Zfas1mentioning
confidence: 99%
“…Askarian-Amiri et al [16] reported ZFAS1 was overexpressed in the mammary gland and down-regulated in breast tumors. Zhang et al [19] found ZFAS1 was negative or weakly expressed in breast cancer. Lee et al [21] found ZFAS1 was downexpression in HER2-positive breast cancer cells.…”
Section: Zfas1 In Various Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there were opposite findings that elevated lncRNA ZFAS1 occurred in gastric cancer, hepatocellular carcinoma and glioma. The function of lncRNA ZFAS1 in cancer cells might be cell type-dependent [12][13][14][15][16][17][18][19][20]. Therefore, we need a systematical and comprehensive meta-analysis to explore whether overexpression of ZFAS1 in tumor are related to worse outcome.…”
Section: Oncotarget 2 Wwwimpactjournalscom/oncotargetmentioning
confidence: 99%